IS SOCIODEMOGRAPHIC PROFILE OF PROJECT-COOPERATOR ESSENTIAL ON THE SUCCESS OF CACAO PLANTATION ESTABLISHMENT? - Vences C Valleser; Glenn R Dayondon; Josephine L Arbes; Andrew B Melencion; Karen Debbie J Cosrojas (Agricultural Socio-Economics Journal, 2020)
The Philippine government is recently reviving its cacao industry. Among the strategies employed is the massive establishment of new cacao plantations. Relative to this, Central Mindanao University was actively involved in the establishment of cacao plantations in its neighboring communities in Bukidnon, Philippines through a project grant from the Philippine Council for Agriculture, Aquatic and Natural Resources, Research and Development (PCAARRD) on August 2016 to July 2019. The project provided assistance to 39 farmers (project-cooperators) who were willing to plant cacao. Sociodemographic profiles of project-cooperators were obtained for possible influence on cacao production. Hence, this study evaluated the influence of sociodemographic profile of project-cooperators on the success of cacao plantation establishment. Prior to the provision of agricultural inputs, our team imparted seminars and trainings on cacao production to project-cooperators. Subsequently, the 39 project-cooperators established new cacao plantations. After the project’s completion on July 2019, we then evaluated the effects of gender, age, marital status, educational attainment, land tenure and main source of income of farmer-cooperators on the success of cacao plantation establishment. Among the sociodemographic factors considered, only land tenure status of project-cooperators was found as essential factor driving the success of cacao plantation establishment. Project-cooperators categorized as land owners resulted to have had satisfactory cacao plantation performance compared to the cacao plantations established by project-cooperators who were just tenants and/or employees. The results could serve as guide to project implementers on the selection of project-cooperators for the success of cacao plantation establishment.